El daño moral en la persona jurídica. Fundamentación jurídica y doctrinaria para que la persona jurídica tenga derecho a la indemnización por daño moral - Cabanillas Hernández, Juriko Catherine (2016)
In developing this thesis my goal was to innovate research work, in order to contribute to the bibliography of the Faculty of Law. I became interested in this issue, which it is relatively new, since until recently the idea that a legal person was liable to compensation for moral damage had not been conceived yet. Therefore, in developing this work in a didactic way - starting from the origin of moral damages to how a legal person is also entitled to compensation for this, and an analysis of our jurisprudence and doctrine both national and comparative - I have the certainty that this research will be a starting point for further study and discussion of the situation in our country. In this forecast, it is necessary that this thesis is not configured as a mere work dedicated exclusively to display or analyze moral damage, as this is something that we have been taught at university classrooms; on the contrary, those criteria that are the basis of the approach of compensation to the legal person subjected to moral damage will be addressed. As such, the criteria considered by the courts to serve as a basis for granting compensation for moral damages in our country will be analyzed, and that becomes the object of analysis of this research